EFEKTIVITAS INDUSTRI EMAS UNTUK MENINGKATKAN PENDAPATAN UMKM (STUDI NASABAH UMKM DI PEGADAIAN NGAWI) - Susandi, Ferix Aziz (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
This research aims to analyze the impact of gold investment at Pegadaian on the income of Micro, Small and Medium Enterprises (MSMEs) in the Ngawi area, East Java and identify what factors influence MSMEs in utilizing gold investment services at Pegadaian Ngawi, as well as what efforts can be made. carried out to increase the participation of MSMEs in gold investment. Data was collected through interviews, observations, documentation and observation. Data analysis is carried out using data reduction, data presentation, and drawing conclusions or verification. Data validity methods use theoretical triangulation, data source triangulation, method triangulation, time triangulation and inter-researcher triangulation. The research results show that PT. Pegadaian (Persero) in Ngawi Regency, East Java, has had a positive impact on MSMEs through gold pawning services, which facilitate access to capital and support local economic growth. Apart from that, Pegadaian also increases financial literacy through education, helping MSMEs understand gold investment. However, MSME participation is still limited due to low financial awareness and accessibility. To overcome this, it is necessary to carry out intensive education, increase access to technology, and transparency in the investment process. This step is expected to make Pegadaian an agent of change for economic growth and financial independence of MSMEs in Ngawi.